Seawater Lamp: Utilization of Seawater as an Alternative Energy Source to Generate Electricity - Kadir, Muh. Ridwan; Arsyad, Nurul Afiqah; Alaydrus, Syarifah Nuraeni; Puspita, Wenny; Sahrul, Sahrul; Agriawan, Muhammad Nurkhalis; Hamzah, Hardi (Universitas Ahmad Dahlan, 2023)
Fishermen are the main livelihood for coastal communities in West Sulawesi. In fishing activities, especially at night, fishermen use lights to attract fish for a greater chance of catching fish. However, fishermen need a supply of electricity to turn on their lights when at sea. Fishermen usually use batteries. This is a significant problem for fishermen because batteries require a relatively high operational level. Researchers found the idea by developing a battery replacement tool to reduce high operating costs. This study aims to utilize seawater as an alternative energy source to overcome the problem of high operational costs for fishermen. The tool developed in this study uses two electrodes (Zn and Cu) placed vertically in a container and then filled with seawater. The two electrodes are connected in series, producing a high output voltage to light an LED. After the initial measurement, the resulting output voltage is 5V and can turn on the LED with a bright enough light. In periodic measurements for 96 hours with data collection every 4 hours, the voltage, current, and power do not decrease significantly, so the seawater lamp is suitable for coastal communities and fishermen's use as lighting when going to sea at night. Series and parallel combinations must be developed to achieve higher voltage and power values ​​and obtain brighter light. The results of this research can be an alternative and renewable energy source that can be widely used.